Stereospecific antiseizure activity in mouse and rat epilepsy models by a pyridinium inhibitor of TNFα/NFκB signaling - Bette S. Pollard; Zhiwei Wen; Kenneth A. Jacobson; John R. Pollard (Elsevier, 2022)
Epilepsy affects over 50 million people worldwide and increases the risk of death. An intrinsic state of central inflammation, mainly driven by TNFα/NFκB signaling, may contribute to the refractory nature of some epilepsies. We have therefore hypothesized that inhibitors of this signaling pathway might be therapeutic. To test this hypothesis, we have measured the antiseizure properties of the enantiomeric compounds MRS-2481 and MRS-2485 in rodent seizure model systems. In the 6 ​Hz (44 ​mA) induced seizure test in mice, the (S) species, MRS-2485, was found to have higher protective potency and lower toxicity than the (R) species MRS-2481. However, neither of these enantiomers were protective in the MES-induced seizure test. MRS-2485 was also found to be protective in the corneal kindled mouse test. Finally, MRS-2485 reduced the post-kainate rat hippocampal slice electrical burst rate and duration. We conclude that MRS-2485, the (S)-enantiomer, is a potent inhibitor of seizure activity in mouse and rat models of epilepsy.